Toxicity Assessment of Ethanol Extract from Castanopsis Costata (Blume.) A. DC Leaves on the Microscopic Structure of White Rat Kidneys - Pratiwi Rukmana Nasution; Zulfikri Zulfikri (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Castanopsis Costata (Blume.) A. DC. leaves are traditionally used for medicinal purposes and are known to be rich in bioactive compounds such as flavonoids, tannins, and alkaloids. However, scientific validation regarding their safety profile remains limited. This study aimed to evaluate the acute toxicity effects of ethanol extract from Castanopsis Costata leaves on the renal histopathology of white rats (Rattus norvegicus). The study used a pretest and posttest in the experimental design method. Twenty-five male rats were randomly assigned into five groups and orally administered the ethanol extract at doses of 5, 50, 300, 2000, and 5000 mg/kg body weight for seven consecutive days. On the eighth day, the rats were euthanized, and kidney tissues were collected for microscopic examination. Data normality and homogeneity were assessed before conducting one-way ANOVA followed by Tukey's HSD post hoc test. Histopathological evaluation revealed no significant morphological alterations in renal tissues across all treatment groups. Statistical analysis confirmed that the data were normally distributed and homogeneous (p > 0.05). One-way ANOVA indicated no significant nephrotoxic effects associated with extract administration across the tested doses (p = 0.023). The ethanol extract of Castanopsis Costata leaves exhibited no observable renal toxicity at doses up to 5000 mg/kg body weight in white rats, suggesting its potential safety for further pharmacological exploration. Future studies should assess sub chronic and chronic toxicity to establish a more comprehensive safety profile Keywords: Castanopsis Costata, Ethanol Extract, Renal Histopathology, Acute Toxicity, White Rats